Evidence for concentration of anthropogenic mercury in salt marsh sediments - C. Micaelo (Ciencias Marinas, 2003)
Sediment cores from two salt marshes, Rosário (Tagus estuary) and Laranjo (Ria de Aveiro), were analyzed for total Hg andAl, and for Fe and Mn extracted with a hydroxylamine-acetic acid solution. Both areas have been contaminated byindustrial discharges during the last decades. Vertical distributions of Hg in sediments colonized by Arthrocnemumfruticosum and Halimione portulacoides were compared to profiles in non-vegetated sediments. The same verticaldistribution pattern was observed in all situations: Hg enriched in sediment layers with high root density. Mercury concentrationsreached 9.3 and 29.1 nmol g1 in Rosário, and 149.0 and 196.0 nmol g1 in Laranjo. At both marshes, higher concentrationswere found in sediments colonized by H. portulacoides. These values are one order of magnitude above the levels found in nonvegetatedsediments. Mercury was enriched in sediment layers containing high concentrations of Fe extracted with ahydroxylamine-acetic acid solution, indicating the importance of Fe (and Mn) oxides formed in the rooting sediments for theretention of anthropogenic Hg.